2021
DOI: 10.1111/zsc.12522
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale population structure within an Eastern Nearctic snake complex (Pituophis melanoleucus)

Abstract: Understanding the processes and mechanisms that promote lineage divergence is a central goal in evolutionary biology. For instance, studies investigating the spatial distribution of genomic variation often highlight biogeographic barriers underpinning geographic isolation or patterns of isolation by environment and isolation by distance that can also lead to lineage divergence. However, the patterns and processes that shape genomic variation and drive lineage divergence may be taxon-specific, even across close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
1
5
1
Order By: Relevance
“…As in Nikolakis et al (2022), the currently recognized subspecies do not correspond to monophyletic groups; however, in contrast to Nikolakis et al (2022), we disagree that this means the subspecies should not be recognized. We do not believe that monophyly or independent lineages (Nikolakis et al 2022) should be expected for subspecific units, as other researchers have reported (Mikles et al 2020, Marshall et al 2021) and as theory predicts (Wilson and Brown 1953, Hillis et al 2021, Dufresnes et al 2023). If subspecific lineages were truly independent, they might be better referred to as species, not subspecies (Wiley 1978; de Queiroz 1998, 2020; Hillis 2020; Dufresnes et al 2023).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…As in Nikolakis et al (2022), the currently recognized subspecies do not correspond to monophyletic groups; however, in contrast to Nikolakis et al (2022), we disagree that this means the subspecies should not be recognized. We do not believe that monophyly or independent lineages (Nikolakis et al 2022) should be expected for subspecific units, as other researchers have reported (Mikles et al 2020, Marshall et al 2021) and as theory predicts (Wilson and Brown 1953, Hillis et al 2021, Dufresnes et al 2023). If subspecific lineages were truly independent, they might be better referred to as species, not subspecies (Wiley 1978; de Queiroz 1998, 2020; Hillis 2020; Dufresnes et al 2023).…”
Section: Discussioncontrasting
confidence: 89%
“…We used 2 genomic methods to understand eastern pinesnake relationships: ultra‐conserved element (UCE) sequencing and restriction‐associated digest sequencing (RADseq, specifically 3RAD; Figure 1). The UCE dataset helped resolve deeper phylogenetic nodes (Faircloth et al 2012), and allowed us to compare our new data to existing eastern pinesnake genomics (Nikolakis et al 2022). The 3RAD dataset allowed us to sequence more individuals, and derive population‐level analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, higher sNMF support for all eastern samples as a single cluster and a linear relationship between genetic and geographical distance for the eastern samples indicates that the structure in the eastern lineage of the L. getula complex ( holbrooki, nigra and getula sensu stricto) is primarily continuous spatial structure, consistent with isolation by distance, rather than discrete lineage structure. A similar pattern was identified in the Eastern Pinesnake ( Pituophis melanoleucus ) complex, which also shows clinal structure across the eastern Nearctic dominated by isolation by distance (Nikolakis et al, 2022). This does not imply that the eastern lineage was not fragmented at some point during glacial cycles or subject to other processes, only that our data do not indicate the presence of multiple discrete lineages at present.…”
Section: Discussionsupporting
confidence: 59%